Designing Legal Frameworks for Public Debt Management - Awadzi, Elsie Addo (IMF Working Papers; Working Paper, 2015)
Sustainable public debt has gained renewed attention as countries implement fiscal consolidation measures in the aftermath of the global financial crisis. Sound public debt policies and debt management practices require robust legal underpinnings. Complex legal issues however arise in the design of the legal framework, and tradeoffs are required in many instances. This paper analyzes key features of modern public debt management legal frameworks, drawing from examples in advanced, emerging, and frontier markets. It aims to provide guidance for countries that seek to review and strengthen their public debt management legal frameworks.